Asas pembangunan sistem - Hamid, Erman (Penerbit UTeM Press, 2024)
The Basics of System Development is a scholarly work related to the basics of information system development. The goal is to be a guide to the developers of information systems at the beginning level, which is aimed at students in the final year of the diploma program in the field of computer science and information technology about procedures and how a system is developed phase by phase.